Atlas of human anatomy - Netter, Frank H.; Hansen, John T. (Teterboro, N.J. : Icon Learning Systems, 2003)
The ultimate anatomy atlas for medical study, clinical reference, and patient education, this updated masterpiece offers 534 of Netter's own accurate, clear and beautifully rendered illustrations along with eight Netter-style drawings rendered by Carlos A.G. Machado, MD. Netter's incomparable medical art and artistry reflects his personal belief in the power of the visual image to teach without overwhelming the student with dense, confusing text. Updated with over 200 revised Netter illustrations, this new edition of the classic human anatomy atlas presents a total of 534 of Netter's own accurate, clear and precisely rendered illustrations along with 8 new Netter-style, surface anatomy drawings by Carlos A.G. Machado, MD. This extraordinary new edition takes a major step forward to include surface anatomy and radiographic images to give a fuller, more integrated understanding of human anatomy. The index is expanded and improved, the references are updated, and a number of images are revised to reflect current knowledge.
Section I. Head and Neck --- Section II. Back and Spinal Cord -- Section III. Thorax -- Section IV. Abdomen -- Section V. Pelvis and Perineum -- Section VI. Upper Limb -- Section VII. Lower Limb -- Section VIII. Cross-Sectional Anatomy -- References -- Index.
Includes bibliographical references and index.
Keywords: HUMAN ANATOMY -- ATLASES